PENGUJIAN ANOMALI PASAR (JANUARY EFFECT) DI BURSA EFEK INDONESIA - Yunita, Ni Kadek Ema; Rahyuda, Henny (E-Jurnal Manajemen, 2019)
The January effect is a phenomenon of deviation from the form of efficient capital markets, where the average return in January is higher than in other months. The purpose of this research is to find out whether there is a January effect on the IDX30 index group companies on the Indonesia Stock Exchange in the period February 2013 to January 2018. This study uses secondary data in the form of monthly stock price data used closing price on the Indonesia Stock Exchange. The sample used was 17 companies. The test results using the SPSS program is a t-test which shows that there is no difference in abnormal stock returns in January with months other than January. So, it can be concluded that the phenomenon of the January Effect does not occur in the Indonesian capital market. Keywords : january Effect, abnormal return, IDX30 Index